The Impact Of Emotional Intelligence And Spiritual Intelligence On Strengthening Students' Character - Agustini, Ria Rizki; Sa’diyah, Maemunah; Husaini, Adian; Hartini, Sri (International Journal of Educational Research & Social Sciences, 2023)
The government always strives to improve the character of the nation's children through its policies and regulations, but the government's efforts have not been fully implemented in every educational environment. The proof is that student character is still in the spotlight. In the field, there are many irregularities, including cases of bullying, brawls causing death, disrespect for teachers, and other things that become homework for educational institutions to strengthen students' character. The solution can be through strengthening spiritual and emotional intelligence. The aim of this research is to find out whether spiritual intelligence and emotional intelligence independently or together influence students' character. And want to know the concept of character education at Tahfidz Cahaya Qur'an High School. The research approach used is a combination method of sequential explanatory models. The results of the research 1) emotional intelligence and spiritual intelligence have a strong relationship and have a significant influence on student character. The dependent variable is more strongly influenced by the independent variables together X1 and character based.